Young consumers’ disconfirmation of expectation and satisfaction with SMEs’ halal food products in the Klang Valley, Malaysia - Abdul Salam, Siti Soleha (2018)
Driven primarily by the growing global Muslim population, the halal industry is expected to become larger in the following years. In tandem with the growth, abundant choices of halal food products are also expected to be available in the market. Therefore, in order to increase the visibility of local halal brands, domestic halal food producers can no longer use their halal status as a competitive advantage. To be able to compete with other brands in the halal marketplace, companies need to revise their strategies and come out with superior products that will be able to meet consumer’s increasing expectation on halal food products. However, previous studies and reports revealed that halal food products produced by small and medium-sized enterprises (SMEs) are still lacking in various aspects. Thus, as a means to improve the products and to meet the changing expectation of Muslim consumer, manufacturers should constantly monitor their consumer’s satisfaction. To date, there is no comprehensive research published that deal with consumer satisfaction towards halal food product in Malaysia neither in general nor segmented into a specific product. Therefore, in order to find out the extent to which consumer expectation had been met, expectancy-disconfirmation theory (EDT) was utilized in this study to examine the discrepancy between consumer expectation and perceived performance on halal food products. Halal confectionery products produced by small and medium-sized enterprises (SMEs) were chosen as the products of analysis. Questionnaires measuring expectation, perceived performance, overall satisfaction and also post-purchase behavioural intention toward SMEs halal confectionery products were administered using convenience sampling within young Muslim consumer in Klang Valley area. A total of 390 usable questionnaire forms were collected and subjected to data analysis. The finding revealed that all the attributes listed experienced negative disconfirmation, which points toward the conclusion that SMEs halal confectionery products were unable to meet their customers’ expectation especially in attributes related to food safety, labelling, and marketing. This study will extend the understanding of SMEs and related parties on Muslim consumer preferences in halal food products, and subsequently, can help in increasing consumer satisfaction. With the reinforcement, local halal food products are expected to claim stronger brand positioning and later on able to penetrate into the global halal market.